2017
DOI: 10.1186/s13722-016-0067-4
|View full text |Cite
|
Sign up to set email alerts
|

Technology-assisted intervention for parents of adolescents in residential substance use treatment: protocol of an open trial and pilot randomized trial

Abstract: BackgroundAdolescents in residential substance use disorder (SUD) treatment have poor outcomes post-discharge, with follow-up studies suggesting that most adolescents relapse within 90 days. Parenting practices directly influence adolescent SUD outcomes, but parents of adolescents with SUDs are difficult to engage in traditional behavioral treatments. The current study adapts and evaluates a technology-assisted intervention for parents of adolescents in residential SUD treatment. Based on pilot qualitative dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 86 publications
0
24
0
1
Order By: Relevance
“… 10 However a recent paper has suggested that higher cut points should be used to reliably identify risky drinkers. 26 In addition, the statistical analyses assumed a similar clustering effect for both treatment conditions at the practice level, through fitting practice level random effects. It could be argued that differences in the intervention could lead to difference in the clustering within practices; however, our assumption a priori, based on substantial relevant experience, was that shared practice characteristics were likely to be the dominant factors in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 10 However a recent paper has suggested that higher cut points should be used to reliably identify risky drinkers. 26 In addition, the statistical analyses assumed a similar clustering effect for both treatment conditions at the practice level, through fitting practice level random effects. It could be argued that differences in the intervention could lead to difference in the clustering within practices; however, our assumption a priori, based on substantial relevant experience, was that shared practice characteristics were likely to be the dominant factors in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…mHealth may be an especially important tool to address disparities in chronic disease outcomes due to high acceptability and accessibility of mobilebased technologies for underserved populations [2,3], including those who are disproportionately affected by the HIV epidemic and are less likely to achieve key clinical outcomes like sustained viral suppression [4]. Through features such as appointment reminders and accessible communication channels with providers, mHealth has been shown to help engage patients lost to or at risk of being lost to care by providing information more efficiently and effectively [5][6][7][8][9][10][11]. Further, features such as medication reminders and self-monitoring of behaviors have been associated with improvements in engagement in care and clinical outcomes [8,12,[13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Although the auto-injector and nasal spray are easy to use and avoid the risk of needle stick injuries, the auto-injector is costly and both have variable insurance coverage. 55 Substance Abuse and Mental Health Services Administration has issued an Opioid Overdose Prevention Toolkit 56 and Prescribe to Prevent (prescribetoprevent.org) provides Continuing Medical Education for medical providers.…”
Section: Tertiary Preventionmentioning
confidence: 99%